TEORI KONFLIK DALAM PERSFEKTIF HUKUM ISLAM: INTERKONEKSI ISLAM DAN SOSIAL - Hayat, Hayat (Institut Agama Islam Negeri (IAIN) Palu, 2013)
Abstract. Â Religion as an ideology in society is believed to allow it to become a paradigm as a solution to conflicts. Islam is a rahmat Â li al-ÄlamÄ«n religion in the life of mankind with conflicts settlement construction in the community as connectivity with customary law (ethics, moral values, character, and culture) and state laws that in fact emerged from the discourse of Islamic law. Religion becomes a balancing of social conflicts that arise from a variety of indicators, because Islam is a legal consensus that includes a variety of conditions and situations of society. Therefore, Islam as a principle regulator of human order become a theory of conflict resolution in the minds of some scientists that suggests an existence of Islam in it.kata kunci: teori konflik. hukum islam, interkoneksi islam dan sosial